THE EFFECT OF CONCENTRATED BALANCE WITH UREA-LIME-M OLASSES STRAW ON DIGESTIBILITY, RUMEN METABOLITES AND BLOOD CHEMICAL OF ETAWAH GOAT BREED - I G. L. O., CAKRA; TRISNADEWI, A. A. A. S.; WIRAWAN, I W. (Majalah Ilmiah Peternakan; Vol 23 No 3 (2020): Vol. 23 No. 3 (2020), 2020)
The research aims to determine the effect of oncentrate balance with urea lime molasses straw (ULMS) on the digestibility, rumen metabolite levels, and blood chemistry has been carried out on Etawah crossbreed goats using a 4 × 4 latin square design. Treatment A (ULMS 60% and concentrate 40%), B (ULMS 50% and concentrate 50%), C (ULMS 40% and concentrate 60%), and D (ULMS 30% and concentrate 70%), were used to carry out this research. The observed variables were consumption of straw and, concentrate, digestibility coefficient, blood chemical levels, rumen metabolites, and rumen microbial population. The results showed that the use of 40-70% concentrate in the Urea-lime-molasses straw ration was insignificantly different from the consumption of dry matter, glucose levels, and blood plasma N urea. Furthermore, there was an increase in nutrient digestibility, triglyceride, total protein, and blood cholesterol, along with the increasing concentrate usage levels. It can be concluded that the use of ULMS as source of fiber of goat up to 60% from dry matter requirenment had no significant different in the consumption of dry matter, glucose levels, and blood plasma N urea.